Implementation of the RADEC Learning Model to Boost Social Studies Learning in Elementary Schools - Denny Ramadhan; Wahyu Sopandi; Arie Rakhmat Riyadi; Neni Maulidah (Global Action and Education for Society, 2026)
This study aims to describe the implementation of the RADEC learning model in enhancing 21st-century skills in the Social Studies (IPS) subject at elementary schools. The research employed a pre-experimental design with a one-group pretest-posttest approach involving fifth-grade students at a public elementary school in Bandung City. The RADEC model was implemented through the stages of Read, Answer, Discuss, Explain, and Create, which are designed to develop students' critical thinking, communication, collaboration, and creativity skills. At the Create stage, the philosophy of positivism serves as an important foundation, where students are encouraged to create based on empirical observation and scientific problem-solving, so that the resulting works are not only innovative but also objectively and empirically testable. The results showed a significant improvement in students' 21st-century skills after the implementation of the RADEC model in Social Studies learning, particularly in creativity based on scientific principles. These findings affirm that the integration of the RADEC model with the positivist approach can encourage students to actively create real solutions in the context of elementary school Social Studies.